Pelajar Minangkabau di Belanda dalam Dua Novel (Tan Sebuah Novel dan Hatta: Aku Datang Karena Sejarah) - David Oktavianus Putra; Mestika Zed; Hendra Naldi (Jurnal Kronologi, 2019)
This article is a historical study that discusses the lives of native Indian students who continued their education to the Netherlands at the beginning of the 20th century depicted in the novel Tan a novel by Hendri Teja and Hatta: I came because of the history written by Sergius Sutanto. Included in historiography research. With the aim of research to see how the novel Tan a Novel and Hatta: I came because History illustrates how the situation of native Indian students who went abroad to the Netherlands in order to seek higher knowledge. This study is a literature study, using a historical qualitative approach with content analysis methods. The conclusion obtained is that the two novels adequately describe the situation of students in the Netherlands. How difficult the journey of these students in studying, ranging from expensive and far away the Netherlands. Cultural and climate differences are very far from those in the Indies. Until the negative views that emerged in Dutch society and the pressure received from the Dutch government due to their movement in fighting for independence. Nevertheless, the two novels describe it differently. This happens due to differences in background owned by the novel writer.